Die Mar̈kte fur̈ Getreide, Ol̈saaten und Kartoffeln - Friedrich Uhlmann (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
– (2) World cereals production in 2000 fell short of the 1999 harvest and most exporting countries ran down stocks. Nevertheless, key world grain prices kept on falling. More and more, genetically modified organisms become an issue to international trade in cereals and oilseeds since importing countries are getting concerned about potential health or environmental risks. In spite of periodically or regionally adverse weather conditions the cereals harvest of EU member countries finally turned out to be the biggest ever - almost 24 mt above domestic use. Due to the price reduction through CAP reform (Agenda 2000), the weak Euro, and less ample supplies in several exporting or importing countries EU producers expected improved export conditions. At the same time, however, EU imports started to increase for matching particular quality requirements of the domestic processing industry.
Keywords: 330